The new koninginins T-U from Phomopsis stipata, an endophytic fungus isolated from Styrax camporum Pohl - Biasetto, Carolina R. [UNESP]; Somensi, Andressa [UNESP]; Sordi, Renata [UNESP]; Chapla, Vanessa M.; Ebrahimi, Samad N.; Silva, Geraldo H.; Teles, Helder L.; Bolzani, Vanderlan da S. [UNESP]; Young, Maria Cláudia M.; Pfenning, Ludwig H.; Araujo, Angela R. [UNESP] (Elsevier, 2020)
Two new polyketides, named koninginin T (1) and U (2), were isolated from Phomopsis stipata - an endophytic fungus isolated from Styrax camporum Pohl. The structures of polyketides 1 and 2 were defined through the analysis of spectroscopic data. Antifungal and acetylcholinesterase inhibitory activities of these compounds were evaluated using TLC bioautographic assays. Compounds 1 and 2 displayed moderate antifungal activity and compound 1 showed acetylcholinesterase inhibitory activity.
Keywords: Acetylcholinesterase inhibitors.; Antifungal; Koninginin; Phomopsis stipata; Polyketides